Regional neurometabolite trajectories and how they relate to neurocognitive - Williams, Simone (Department of Paediatrics and Child Health, 2024)
Introduction Since perinatal neurodevelopment forms the basis upon which optimal brain health and function are built, exposure to maternal HIV and/or antiretroviral therapy (ART) during in utero and/or early postnatal development may adversely affect functional brain development and subsequent neurological functioning, in children who are exposed to HIV and/or ART perinatally. Regional brain metabolite alterations have previously been linked to HIV exposure in both young and older children, however, it is not yet known whether neurometabolite profiles may be related to impaired functional neurodevelopment, often observed in children exposed to HIV and/or ART. This study thus explored regional brain metabolite concentrations in 6-year-old children who are HIV-exposed uninfected (CHEU) compared to children who are HIV-unexposed (CHU), and explored associations of neurometabolite profiles with functional neurodevelopmental outcomes in CHEU. Methodology At baseline a total of 1143 infants (from 1137 women) were included in the DCHS, 248 CHEU and 895 CHU (matched controls). A subset of 152 children enrolled in the DCHS had magnetic resonance spectroscopy data acquired at 6 years of age, 42 CHEU and 110 CHU . Absolute and relative brain metabolite concentrations were quantified from single voxels covering parietal grey matter (pgm) and right parietal white matter (pwm). Functional neurodevelopmental outcomes were also assessed at 6 years of age, using the Early Learning Outcome Measures (ELOM) tool. Neurometabolite concentrations between CHEU and CHU groups were compared using adjusted linear regression analysis. Underlying neurometabolic patterns based on MRS data were identified using factor analysis, and the relationship between neurometabolite patterns and HIV and/or ART exposure status was explored using logistic regression analysis. This study also used Pearson correlation analysis to explore the relationship between neurometabolite factors associated with HIV and/or ART exposure status, as well as individual neurometabolite concentrations, and ELOM subdomains in CHEU and CHU. Results After quality control, 138 and 109 usable MR spectra for pgm (98 CHU, 40 CHEU, 53% male) and pwm (84 CHU, 25 CHEU, 55% male) were available, respectively. CHEU were on average one month older than CHU, with age ranging from 69 to 81 months. All mothers of CHEU received ART. In pgm, both absolute and relative glutamate concentrations were significantly lower in CHEU compared to CHU, after adjusting for maternal alcohol use using pregnancy, child sex and child age at scan (p = 0.046 and p = 0.035 for absolute and relative glutamate respectively). Similarly, adjusted relative choline concentrations in pwm were also significantly lower in CHEU (p = 0.039). Factor analysis identified four underlying neurometabolite patterns from both relative and absolute MRS data. A pgm glutamate and myo-inositol dominated factor, identified from the relative MRS data, was associated with HIV and/or ART exposure status in unadjusted (OR 0.55, 95% CI 0.17 - 0.45, p = 0.013) and adjusted analyses (OR 0.59, 95% CI 0.35 - 0.94, p = 0.031 ). A significant correlation between the pgm glutamate and myo-inositol dominated factor associated with HIV exposure and ELOM gross motor development scores in CHEU (r = -0.48 , p= 0.044) was also observed. This association was not found to be statistically significant in CHU. Significant associations between individual neurometabolite concentrations and ELOM outcomes in CHEU and CHU were also found in this study. Discussion Reduced glutamate concentrations in parietal grey matter suggest regional alterations in excitatory glutamatergic transmission pathways in the context of perinatal HIV and/or ART exposure, while reduced choline concentrations in parietal white matter may suggest regional myelin loss. The ability to detect neurometabolite patterns in this study may suggest that brain metabolites are integrated and function together under specific physiological or pathological conditions. Furthermore, the identified association between the pgm glutamate and myoinositol pattern associated with HIV exposure and gross motor development outcomes, provides an understanding of a potential mechanism which may underlie adverse functional neurodevelopmental symptomology in CHEU.